OP0188-PC Pain trajectories in hip osteoarthritis: Results of the dutch cohort hip and cohort knee (CHECK). (23rd January 2014) - Verkleij, S.P.; Luijsterburg, P.A.; Wesseling, J.; Bastick, A.N.; Koes, B.W.; Bierma-Zeinstra, S.M.
Abstract : Background: Pain is the most important complaint reported in osteoarthritis (OA). In hip OA, a recent study showed five distinctive trajectories of pain over a two year follow-up period.[1] The next step is to validate these finding in another study population with a longer follow-up period. Objectives: To identify long term trajectories of persons with hip pain due to OA over a 5-year follow-up period. Methods: Data from the inception cohort CHECK[2] was used to investigate the course of pain. For this study 208 participants were included who fulfilled the clinical and/or radiographic American College of Rheumatology (ACR) criteria for hip OA. Participants filled out yearly questionnaires during the 5-year follow-up period. Pain severity was measured by an 11-point numeric rating scale (0=no pain;10=unbearable). Latent class growth analysis (LCGA) was used to determine the number of different trajectories of participants with hip pain due to OA. Multinomial regression analysis was used to predict the effect of baseline characteristics of the participants and the probability of membership to a one of the trajectories. Results: Analyses yielded 4 distinctive trajectories of pain during the five year follow-up instead of five trajectories in another study sample over two years of follow-up. Participants within trajectory 1 ("mild pain"; n=78) fluctuated slightly within ranges of mild pain. Trajectory 2 ("moderate pain"; n=76) consists of participants who slowly increased within ranges of moderate pain over the 5-year period. Trajectory 3 ("decreasing pain"; n=22) comprised participants who started with severe pain at baseline, but after 5-years their pain decreased. Participants within trajectory 4 ("always pain"; n=32) had constant levels of severe pain. Compared with the "mild pain" group, participants in the "moderate pain" group have a higher body mass index (BMI), more often have morning stiffness of the hip, a decreased hip flexion, and concurrent knee complaints. Participants in the "always pain" group are more likely to be women. Conclusions: LCGA identified 4 distinct trajectories in 208 participants with clinically and/or radiographic determined hip OA. Predictors for membership to the "moderate pain" group were BMI, morning stiffness of the hip, decreased hip flexion, and concurrent knee pain. For the "always pain" group this was gender. References: Verkleij SPJ, Hoekstra T, Rozendaal RM, Waarsing JH, Koes BW, Luijsterburg PAJ, Bierma-Zeinstra SMA. Defining discriminative pain trajectories in hip osteoarthritis over a two-year time period. Ann Rheum Dis 2012. Wesseling J et al. CHECK (Cohort Hip and Cohort Knee): similarities and differences with the Osteoarthritis Initiative. Ann Rheum Dis 2009;68:1413-9. Disclosure of Interest: None Declared